2000
DOI: 10.1081/ddc-100101278
|View full text |Cite
|
Sign up to set email alerts
|

Permeation Studies Comparing Cobra Skin with Human Skin Using Nicotine Transdermal Patches

Abstract: Cobra skin (Naja Naja Khaotia) was used as a barrier for an in vitro permeation study using nicotine. Fluxes of nicotine that permeated from Nicotinell through cobra skin (CS) taken from the head, body, and tail were 233.93 +/- 16.08, 206.87 +/- 19.00, and 211.26 +/- 22.93 micrograms/cm2/hr1/2, respectively (n = 6). This indicated no significant difference (p > .05). Abdominal human epidermis (HE), obtained from cadavers, and the CS provided identical permeation kinetics for nicotine, which can be described by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 12 publications
3
6
0
2
Order By: Relevance
“…Inter-specimen variation of human epidermis was higher than that of shed snake skin. This result was similar to previous reports (Southwell et al 1984 ;Pongjanyakul et al 2000). Human skin had greater inter-specimen variation because of the variation of hair follicles (Bialik et al 1993) and the thickness of epidermis (Whitton & Everall 1973).…”
Section: Nicotine Permeation Studysupporting
confidence: 92%
See 2 more Smart Citations
“…Inter-specimen variation of human epidermis was higher than that of shed snake skin. This result was similar to previous reports (Southwell et al 1984 ;Pongjanyakul et al 2000). Human skin had greater inter-specimen variation because of the variation of hair follicles (Bialik et al 1993) and the thickness of epidermis (Whitton & Everall 1973).…”
Section: Nicotine Permeation Studysupporting
confidence: 92%
“…This indicated that the matrix skin system formed a single homogenous polymeric ® lm. The results were similar to those using whole cobra skin as a membrane in a previous study (Pongjanyakul et al 2000). The equation used to describe the transport of nicotine across the three types of membrane is as follows (Kydonieus 1987):…”
Section: Nicotine Permeation Studysupporting
confidence: 85%
See 1 more Smart Citation
“…Cobra skin was used as a barrier membrane for the DS permeation studies because one snake skin provides enough material for a complete study, with low intraspecimen variation (Pongjanyakul et al 2000). The whole skin of a cobra (Naja Naja Khaotia) was obtained within 24 h after its natural death from the Snake Farm, Thai Red Cross, Bangkok, Thailand.…”
Section: Skin Preparationmentioning
confidence: 99%
“…Existe, também, uma terceira e última camada de alfa-queratina mais interna. A camada intermediária é subdividida em três subcamadas de estrutura multilamelar com células cornificadas (alfa-queratina), ao redor dos lipídeos intercelulares, representando, assim, o principal depósito de lipídeos, sendo considerada a maior barreira para a penetração da água (Pongjanyakul et al, 2000).…”
Section: Papaínaunclassified